A Walrus Joins In - Puttock, Simon (Oxford Oxford University Press, 2014)
In Walrus Joins In everyone in the North Pole is very excited about the 'Big Show in the Snow'. Anyone can be in it. The trouble is, Walrus wants to take part... TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: a